KP-Lab System for the Support of Collaborative Learning and Working Practices, Based on Trialogical Learning - Paralič, J.; Babič, F.; Wagner, J.; Bednár, P.; Paralič, M. (Informatica)
KP-Lab System for the Support of Collaborative Learning and Working Practices, Based on Trialogical Learning